Kuat Tekan Dan Porositas Beton OPC Dan OPC POFA Dengan Air Pencampur Gambut Menggunakan Bahan Aditif - Ridho Rinanda; Monita Olivia; Edy Syaputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water often used as concrete mixing water in areas that are difficult to get clean water. The characteristic of peat water are acidic and has low pH value, so it is not recommended to use as concrete mixing water because it can reduce the quality of concrete. Material of mineral like Palm Oil Fuel Ash (POFA) used in concrete mixture can imvrove the density and strenght. Beside the addition of mineral materials, improvement of water quality concrete mixer can also improve the quality of concrete. The purpose of this reserach to quantify the compressive strength and porosity of the concrete where the concrete mixing water used is water that has been processed peat. The peat water treathment is acidid neutralized by the alkaline additives. The pH value used as parameter to improve the quality of water by adding additives such as quicklime. The type of cement used in concrete mix OPC and OPC POFA 10%. Peat water in this research from Rimbo Panjang, Kampar and POFA comes from PT. Tarera Bangun Riau, PKS Perhentian Raja, Kampar regency. The result showed that the peat water’s quality has been improved with addition of quicklime will produce the quality of concrete is better than the using peat water without repair.Keywords : Phsycal properties, OPC, POFA (palm oil fuel ash), peat water, additive, quicklime, peat field condition.